Integration of Islamic Financial Technology and Digital Financial Inclusion in Indonesia - Rofik, Moh.; Huda, Nurul (Journal of Economics and Social Sciences (JESS), 2025)
The development of financial technology (FinTech) has opened significant opportunities to expand access to inclusive financial services, including within the Islamic finance ecosystem. This article examines how the integration of Islamic financial technology (sharia fintech) can enhance digital financial inclusion among Indonesian society throughout 2021–2025. Using a literature review approach based on academic research, regulatory reports (OJK), and international institutional publications, the findings indicate that sharia fintech has the potential to expand the reach of Islamic financial services, particularly for MSMEs, marginalized communities, and younger generations. However, major challenges include low Islamic financial literacy, regulatory gaps for digital sharia products, as well as data security and sharia governance issues. Recommendations include regulatory harmonization, enhancement of digital–sharia literacy, development of governance standards and sharia compliance certification for digital products, and incentives for platforms that integrate maqasid al-shariah principles and inclusion indicators.